Resolving NGC 3198’s rotation curve with quantum gravity ‎theory: a dark matter-free framework - WONG, Wing To; WONG, Wing-Keung (International Journal of Advanced Astronomy, 2025)
The rotation curve of NGC 3198, a well-studied spiral galaxy, exhibits a flat velocity profile at large radii that cannot be explained by Newtonian dynamics based on visible mass alone. The researchers apply the new Quantum Gravity Theory (QGT), which incorporates graviton-antigraviton interactions, to model the galaxy’s kinematics without invoking dark matter. Using HI data from *The HI Nearby Galaxy Survey* (THINGS), the researchers calculate the gravitational scale-length and derive the quantum-corrected velocity . The QGT-predicted rotation curve matches observations with residuals < 5 km/s and , demonstrating that QGT provides a robust, first-principles explanation for NGC 3198’s dynamics.